FUNGSI DPRD DALAM PROSES PEMBUATAN KEBIJAKAN PUBLIK (Studi Kasus di Kota Sungai Penuh): Awal Khairi - Khairi, Awal (Qawwam : The Leader's Writing, 2020)
In carrying out its function as people's representatives, the Regional People's Representative Council has a function in the process of making public policies to increase knowledge of government in society. In addition, public policies can make people more fully participate in a government system. This function has been adjusted to the understanding of democracy and people's sovereignty where the people must carry out their duties as government participants in Sungai Penuh City. The formulation of the research problem is, What is the Function of the DPRD in the Public Policy Making Process (Case Study in Sungai Penuh City)? The research objective is to determine the function of DPRD in the Public Policy Making Process (Case Study in Sungai Penuh City). This research uses a qualitative approach where data is obtained through field interview guides to 5 informants referring to 5 research indicators, namely 1. Agenda setting process 2. Policy formulation process 3. Policy adoption process 4. Policy implementation process and 5. Policy evaluation process. The data obtained in the field were analyzed based on the classification of the informants' answers which were described in the results and discussion of the research which was then carried out by the interpreter of the researcher. It is known that the function of DPRD in the Public Policy Making Process (Case Study in Sungai Penuh City) of the five research indicators four indicators are well implemented, namely for the indicators of the policy formulation process, the policy adoption process, the policy implementation process, and the policy evaluation process while the process indicators The formulation of policies has not been carried out properly and this is in line with the theory of Purwo's opinion which the author makes as a proposal in research indicators. For this reason, the authors suggest that the function of DPRD in the Public Policy Making Process in Sungai Penuh City can be improved so that it can be maximized in carrying out its function in policy making.